Measuring and managing franchisee satisfaction: a study of academic franchising / Firdaus Abdullah... [et al.] - Abdullah, Firdaus; Alwi, Mohd Rashidee; Lee, Nagarajah; Voon, Boo Ho (2006)
Franchise satisfaction is crucial to franchise management, and it is considered to be a central variable for the franchise network's long-term survival. While an abundance of research exists on the topic of franchising, none has been directed toward measuring franchisee satisfaction within an academic setting, and this despite the increasingly large number of tertiary institutions offering programs on franchise arrangement. Although there were initiatives to develop a new measuring instrument of satisfaction for the franchise industry, such generic scale was not suited to the unique nature of academic franchising. Therefore, this study attempts to explore different approaches of franchisee satisfaction within an academic setting, develop and validate a new measuring instrument, examine the key factors and their influence on performance and intention to remain in the network, and eventually manage the franchise network for long-term continuity. This study was conducted in Malaysia over a sample of 68 respondents representing 19 franchised colleges within MARA University of Technology's (UiTM) network. The findings suggest five dimensions of franchisee satisfaction namely social interaction, service support, financing, assurance and competence. Hence, UiTM should be able to ascertain the level of services provided, and to determine which dimensions need improvement. Knowing the strengths and weaknesses of these dimensions and their relative influence may result in better allocation of resources so as to provide a better service to the franchised colleges. This study has also sought to contribute further to the growing literature on franchising by advancing a new 23-item measuring instrument, which is specifically tailored for academic franchising.